2023
DOI: 10.3389/fpls.2023.1193905
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplets are versatile organelles involved in plant development and plant response to environmental changes

Imen Bouchnak,
Denis Coulon,
Vincent Salis
et al.

Abstract: Since decades plant lipid droplets (LDs) are described as storage organelles accumulated in seeds to provide energy for seedling growth after germination. Indeed, LDs are the site of accumulation for neutral lipids, predominantly triacylglycerols (TAGs), one of the most energy-dense molecules, and sterol esters. Such organelles are present in the whole plant kingdom, from microalgae to perennial trees, and can probably be found in all plant tissues. Several studies over the past decade have revealed that LDs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 215 publications
(294 reference statements)
0
6
0
Order By: Relevance
“…However, at 5-6 um (Fig. 3D), the lipid bodies are at the top of the size range reported for stress-induced leaf plastoglobules (Arzac, Fernández-Marín, and García-Plazaola 2022; Bouchnak et al 2023), but common for cytosolic lipid droplets (C. Xu, Fan, and Shanklin 2020).…”
Section: Discussionmentioning
confidence: 77%
“…However, at 5-6 um (Fig. 3D), the lipid bodies are at the top of the size range reported for stress-induced leaf plastoglobules (Arzac, Fernández-Marín, and García-Plazaola 2022; Bouchnak et al 2023), but common for cytosolic lipid droplets (C. Xu, Fan, and Shanklin 2020).…”
Section: Discussionmentioning
confidence: 77%
“…LDs are not merely energy storage organelles, but also dynamic structures involved in diverse cellular metabolisms like membrane remodelling, regulation of energy homeostasis, stress responses and coordination between different organelles ( Choi et al 2022 ; Bouchnak et al 2023 ). In addition, they play crucial roles at key sites in the freezing tolerance of seeds, engaging in direct interaction with glyoxysomes for seedling lipid degradation and producing antifungal compounds in leaves ( Shimada et al 2018 ; Olzmann and Carvalho 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that LDs are dynamic structures that play essential roles in cellular activities. These findings have revealed the multifunctionality of LDs within cells [247]. Abiotic stress can cause changes in nutrient availability and energy demands in cells, which can lead to alterations in TAG accumulation.…”
Section: Cell Membrane Lipid and Triglycerides Accumulated In Lipid D...mentioning
confidence: 84%